ELK3 modulates the antitumor efficacy of natural killer cells against triple negative breast cancer by regulating mitochondrial dynamics. Issue 7 (20th July 2022) - Park, Joo Dong; Kim, Kwang-Soo; Choi, Seung Hee; Jo, Gae Hoon; Choi, Jin-Ho; Park, Si-Won; Ko, Eun-Su; Lee, Minwook; Lee, Dae-Keum; Jang, Hye Jung; Hwang, Sohyun; Jung, Hae-Yun; et al.
Abstract : Background: Triple negative breast cancer (TNBC) is the most lethal subtype of breast cancer due to its aggressive behavior and frequent development of resistance to chemotherapy. Although natural killer (NK) cell-based immunotherapy is a promising strategy for overcoming barriers to cancer treatment, the therapeutic efficacy of NK cells against TNBC is below expectations. E26 transformation-specific transcription factor ELK3 (ELK3) is highly expressed in TNBCs and functions as a master regulator of the epithelial-mesenchymal transition. Methods: Two representative human TNBC cell lines, MDA-MB231 and Hs578T, were exposed to ELK3-targeting shRNA or an ELK3-expressing plasmid to modulate ELK3 expression. The downstream target genes of ELK3 were identified using a combined approach comprising gene expression profiling and molecular analysis. The role of ELK3 in determining the immunosensitivity of TNBC to NK cells was investigated in terms of mitochondrial fission–fusion transition and reactive oxygen species concentration both in vitro and in vivo. Results: ELK3-dependent mitochondrial fission–fusion status was linked to the mitochondrial superoxide concentration in TNBCs and was a main determinant of NK cell-mediated immune responses. We identified mitochondrial dynamics proteins of 51 (Mid51), a major mediator of mitochondrial fission, as a direct downstream target of ELK3 in TNBCs. Also, we demonstrated that expression of ELK3 correlated inversely with that of Mid51, and that the ELK3-Mid51 axis is associated directly with the status of mitochondrial dynamics. METABRIC analysis revealed that the ELK3-Mid51 axis has a direct effect on the immune score and survival of patients with TNBC. Conclusions: Taken together, the data suggest that NK cell responses to TNBC are linked directly to ELK3 expression levels, shedding new light on strategies to improve the efficacy of NK cell-based immunotherapy of TNBC.